Research and Development of P22 Seamless Steel Pipe with Large Diameter and Medium Thick Wall Based on the Φ820mm Precision Skew Rolling Mill - Zheng Shijian, Xu Lujun, Han Renlong, Chen Siying (Teshugang)
This article mainly introduces the process flow, process difficulties, and innovative points of hot-rolled direct production of large-diameter medium thick wall P22 seamless steel tubes with a diameter of over Φ 900mm. This research and development has the advantages of short process flow, low production cost, high yield, The steel pipe has precise dimensions, good surface quality, and excellent performance. Base-d on the P22 seamless steel pipe produced by Φ820mm precision inclined rolling mill ,combined with the requirement of grade 12Cr2MoG in GB/T 5310-2023 ,,the relevant indicators of P22 seamless steel pipes were analyzed through surface quality inspection, physical and chemical inspection and other methods.After testing, the produced P22 seamless steel pipe had properties as outer diameter deviation of -0.5mm-+6.2mm, ovality of 0.58%, wall thickness deviation of -8.7%-+10.3%, uneven wall thickness of 13.42%, tensile strength of 513 MPa, ,511 MPa, yield strength of 318, MPa, 311 MPa, elongation of 34.0%,33.0%, eaverage impact energy of 257J,242 J at room temperature , average hardness of 153/152 HBW, microstructure of ferrite+bainite+a small amount of pearlite, grain size of 6.0-7.0, and ductile brittle transition temperature below -40 ℃; The results indicate that the chemical composition and various properties of large diameter medium thick walled P22 seamless steel pipes produced by the Φ 820 mm precision skew rolling mill meet the requirements of ASTM A 335/A 335M-24b and other standards.